American Wages - Wolman, Leo (Quarterly Journal of Economics, 1932)
Journal Article American Wages Get access Leo Wolman Leo Wolman Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 46, Issue 2, February 1932, Pages 398–406, https://doi.org/10.2307/1883238 Published: 01 February 1932